ANALYSIS OF PAPER RAW MATERIAL EFFICIENCIES FOR INFORMA BROCHURE IN THE PRINTING PRODUCTION - Yessy Yerta Situngkir (Politeknik Negeri Media Kreatif, 2019)
Efficient use of paper raw materials in the printing business is simple but important. This research was conducted to provide information that to get a low production price, the amount of raw materials and the selection of raw materials used must be precise. One of the raw materials needed in printing production is paper. The results of testing the efficiency of the use of paper for printing brochures Informa with 5000 sheets of brochure is the use of flipchart paper with a size of 65x100 cm. It takes 117.98 kg or Rp. 1,651,650, - to buy raw materials of paper. Waste from the use of paper raw material is 24.73 kg or Rp. 346,150. In addition to the very small waste generated, the price of brochure printing is also cheaper compared to the other flip size of Plano is Rp. 1,023.15,-..